Electro-acupuncture reduced steatosis on MRI-PDFF in patients with non-alcoholic steatohepatitis: a randomized controlled pilot clinical trial - Jingjie Zhao; Qianyi Wang; Xinyu Zhao; Lina Wu; Juanjuan Li; Wen Zhang; Shuai Xu; Chaoru Han; Yi Du; Xiaofei Tong; Weijia Duan; Di Cao; et al. (BMC, 2023)
Abstract Background Non-alcoholic steatohepatitis (NASH) had not yet been approved therapy. Electro-acupuncture (EA) has been reported to have potential efficacy. However, high-quality clinical evidence was still lacking. Methods NASH patients were randomized and allocated to either sham acupuncture (SA) or EA group in a 1:1 ratio, with the patient blinded. Each patient received 36 sessions of SA or EA treatment over 12 weeks, followed by additional 4 weeks. The primary outcome was the changes in relative liver fat content measured by magnetic resonance imaging proton density fat fraction (MRI-PDFF). Results A total of 60 patients were enrolled. From baseline to week 12, the reduction of relative liver fat content measured by MRI-PDFF in the EA group (− 33.6%, quantile range: − 52.9%, − 22.7%) was significantly more significant than that in the SA group (− 15.8%, quantile range: − 36.1%, − 2.7%) (p = 0.022). Furthermore, the EA group had more patients who achieved MRI-PDFF to 30% reduction at week 12 (53.3% vs. 25.9%, p = 0.035). EA treatment also significantly reduced body weight (− 3.0 vs. + 0.1 kg, p = 0.034) and BMI (− 1.5 vs. − 0.2 kg/m2, p = 0.013) at week 16. Except for AST (− 27.4 vs. − 16.2 U/L, p = 0.015), other biochemical varieties, including ALT, fasting-glucose, cholesterol, and triglyceride, showed no statistically significant difference. Both groups measured no significant changes in liver stiffness by magnetic resonance elastography (MRE). There were no serious adverse events in either group. Conclusions Twelve weeks of EA effectively and safely reduces relative liver fat content in NASH patients. Further multicenter randomized controlled studies are needed. Trial registration Chinese Clinical Trial Registry, ChiCTR2100046617. Registered 23 May 2021, http://www.chictr.org.cn/edit.aspx?pid=127023&htm=4